The Urgency of Modifying Regulations for the Safety of General Election Organizers in 2024 - Hamzah, Moh. Zulkarnaen; Darmawati, Darmawati; Makkulawuzar, Kingdom (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2024)
General elections in Indonesia have been held 12 times, namely in 1955, 1971, 1977, 1982, 1987, 1992, 1997, 1999, 2004, 2009, 2014 and 2019. And, the general election simultaneously and costing not a few lives occurred in 2019. Basically, the simultaneous general elections held in 2019 had many irregularities, especially the large number of members of ad hoc election organizers who fell ill and died. This happened in almost every region. Does the 2019 general election have anything to do with the increased workload of ad hoc election organizers due to the simultaneous implementation? Type of research uses normative legal research methods. It is called so, because normative research focuses on prescriptive research, using secondary data such as laws and regulations, legal theories, legal principles, and scientific works of legal scholars. The problems that occurred in the 2019 general election can be anticipated by making adequate regulatory modifications in order to create a rational, humane authority, and better election management than the previous period. There needs to be a guarantee of the quality of direct, general, free, secret, honest and fair elections. The implementation of simultaneous elections has provided a heavy workload, long implementation time and very tiring manual vote counting. Members of the voting and counting organizing group need to be protected by making some kind of regulation in their favor.___ References Books with an author: Gaffar, Janedjri M. (2013). Demokrasi dan Pemilu di Indonesia, Jakarta: Konstitusi Press. Indra, M. (2011). Dinamika Hukum Tata Negara Indonesia, Bandung: PT Refika Adiatma. Ramadhanil, F., Pratama, H. M., Salabi, N. A., & Sadikin, U. H., (2019). Evaluasi Pemilu Serentak 2019: Dari Sistem Pemilu ke Manajemen Penyelengaraan Pemilu, Jakarta: Perkumpulan untuk Pemilu dan Demokrasi (Perludem). Suharizal. (2012). Pilkada, Regulasi, Dinamika dan Konsep Mendatang, Jakarta: Rajawali Pers. Suyanto. (2023). Metode Penelitian Hukum Pengantar Penelitian Normatif, Empiris dan Gabungan, Gresik: Unigres Press. Journal articles: Abbas, A., & Dompak, T. (2020). Dampak Demokrasi terhadap Kesejahteraan (Studi Kasus di Indonesia). Dialektika Publik, 5(1), 43-49. https://doi.org/10.33884/dialektikapublik.v5i1.2417 Carney, G. (2015). Comparative Approaches to Statutory Interpretation in Civil Law and Common Law Jurisdictions. Statute Law Review, 36(1), 46-58. https://doi.org/10.1093/slr/hmu019 Dwianto, A., & Makhali, I. (2024). Analisis Penerapan Asas Langsung, Umum, Bebas, Rahasia, Jujur, dan Adil terhadap Pemilihan Wakil Bupati Tulungagung Sisa Masa Jabatan 2018-2023. Mizan: Jurnal Ilmu Hukum, 13(1), 29-44. ttps://doi.org/10.32503/mizan.v13i1.5329 Hariati, S., Nasution, M. A., & Warjio, W. (2021). Analisis Faktor Eksternal yang Mempengaruhi Beban Kerja Kelompok Penyelenggara Pemungutan Suara pada Pemilihan Umum 2019. PERSPEKTIF, 10(2), 467-474. https://doi.org/10.31289/perspektif.v10i2.4616 Hofi, M. A., & Wicaksono, T. (2023). Menjaga Eksistensi Kedaulatan Rakyat Dalam Bidang Politik, Hukum, dan Ekonomi. Hakim: Jurnal Ilmu Hukum dan Sosial, 1(3), 141-153. https://doi.org/10.51903/hakim.v1i3.1235 Mustawa, M., Hamid, A. H., & Purwanda, S. (2022). Refund of State Financial Losses in Realizing the Welfare State of Law. Amsir Law Journal, 4(1), 51-61. https://doi.org/10.36746/alj.v4i1.125 Purwanda, S., Ambarwati, A., Darmawati, D., & Prayudi, P. (2024). Haluan Kesejahteraan Sosial Dalam Diskursus Teori-Teori Keadilan. Dinamika Hukum, 25(1), 152-161. https://doi.org/10.35315/dh.v25i1.9819 Putri, N. H., Laia, A., & Laia, B. (2023). Sistem Proporsional Pemilihan Umum Dalam Perspektif Politik Hukum. Jurnal Panah Keadilan, 2(2), 66-80. https://doi.org/10.57094/jpk.v2i2.1006 Ratama, R., Situmorang, T. P., & Ginting, B. (2023). Analisis Kinerja Kelompok Penyelenggara Pemungutan Suara (KPPS) dalam Pemilihan Umum Tahun 2019 di Kabupaten Tapanuli Utara. PERSPEKTIF, 12(3), 1030-1042. https://doi.org/10.31289/perspektif.v12i3.9731 Ridlwan, Z. (2011). Negara Hukum Indonesia Kebalikan Nachtwachterstaat. Fiat Justisia: Jurnal Ilmu Hukum, 5(2), 141-152. https://doi.org/10.25041/fiatjustisia.v5no2.56 Sumanto, D., & Nggilu, S. (2020). Kedudukan Peraturan Komisi Pemilihan Umum (PKPU) Dalam Tata Susunan Peraturan Perundang-undangan Republik Indonesia. Datuk Sulaiman Law Review (DaLRev), 1(1), 27-38. https://doi.org/10.24256/dalrev.v1i1.1594 Tarina, U., Febrian, M. R., Prihastuti, I. C., & Nurcahya, W. F. (2024). Efektivitas Penyerapan Anggaran Belanja Negara Dalam Pemilihan Umum. Journal of Law, Administration, and Social Science, 4(5), 785-797. https://doi.org/10.54957/jolas.v4i5.885 Wijaya, S., Amiruddin, S., & Budiati, A. (2023). Strategi Komisi Pemilihan Umum Kabupaten Pandeglang untuk Meningkatkan Partisipasi Pemilih Dalam Pilkada Serentak di Kabupaten Pandeglang Tahun 2020. Jurnal Cahaya Mandalika, 4(3), 335-349. https://doi.org/10.36312/jcm.v4i3.1788